Formal Verification Issues For Component-Based Development (Informatica, 2020)
Component-based development has made a breakthrough in software industry, it offers safer systems and easier to maintain, furthermore, costs and time to market are reduced. However, several issues, such as the correctness of component-based systems, their adaptation or the interactions between their components, require rigorous verification through the use of formal methods and tools.In this paper, we first present an introduction to component-based development; afterward we propose a classification of formal verification issues for component-based systems.